Orientalism and the British Picture Postcard Industry: Popularizing the Empire in Victorian and Edwardian Homes - Gilles Teulié (Cahiers Victoriens et Edouardiens)
During the 19th century as and when Europeans developed a keen interest in what was described as the ‘Orient’—ranging from architecture in Moorish Spain to the faces and places in Northern Africa and the Middle East–—images of an exotic fantasised Orient bounced back to Europe, in particular through the works of artists who painted what they had seen, or thought they had seen. The Orientalist movement was buttressed by Napoleonic expeditions in Egypt or the travel boom (Eugène Delacroix in Morocco). And yet suffice it to say that only the elite had access to these visual representations, either by becoming owners of paintings or by admiring them in art galleries, the prerogative of the educated and the wealthy. It is against this context that the article will consider how ‘high culture’ and ‘popular culture’ (and particularly postcards) permeated Victorian and Edwardian society, and through the transformative power of the Arts, contributed eminently to the consolidation of the imperial project.